1996
DOI: 10.1159/000177911
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Energy between Food-Restricted Dams and Offspring

Abstract: Pregnant and nonpregnant rats were subjected to one of four food intake schedules: ad libitum, 20, 40 and 60% of food restriction, during 20 days, with the objective of studying the distribution of energy between food-restricted mothers and offspring. The animals were anesthetized and the conceptuses were removed and separated into male, female, and placental tissues. The rats were then killed and all carcasses were prepared for energy balance determination. A baseline group of weight-matched rats were killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The present study showed that the offspring of food-restricted dams exhibited lower body weight than those of control dams. These results replicate previous findings from our group (Luz and Griggio, 1996;Griggio et al, 1997;Luz et al, 2003), and suggest that the mother transfers part of her nutritional deficit to the offspring in order to keep survival.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that the offspring of food-restricted dams exhibited lower body weight than those of control dams. These results replicate previous findings from our group (Luz and Griggio, 1996;Griggio et al, 1997;Luz et al, 2003), and suggest that the mother transfers part of her nutritional deficit to the offspring in order to keep survival.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, around 40% of the reduction in energy expenditure was always present and it was independent of age [12,17] or pregnancy [11,13] . For the first time, the pres- ent experiment has shown a situation (MSG obesity) in which the mechanism of energy conservation was reduced by !…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in energy expenditure during food restriction or fasting is very well documented [11,13,17,29] and represents a mechanism of energy conservation, which is fundamental for the animal's survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations